Setup uncertainty of head and neck cancer (HNC) patients treated with Image Guided and Intensity Modulated Radiotherapy (IG-IMRT) - Nada Alia M Zamri; Hafiz M Zin (Journal of Medical Physics and Biophysics, 2017)
Advances in radiotherapy technology has made it possible to deliver highly conformal beams such as Intensity Modulated Radiotherapy (IMRT). The treatment is often guided by on-board cone-beam CT (CBCT) imaging system known as Image Guided Radiotherapy (IGRT). This retrospective study investigates the reproducibility of treatment setup for 25 head-and-neck cancer (HNC) patients underwent IMRT treatment at a new centre using kiloVoltage CBCT based-IGRT. All patients were immobilised using the HeadSTEPTM iFRAME. The planning target volume (PTV) margin was set to 3 mm for all directions during treatment planning. The pre-treatment CBCT imaging was acquired after patient setup. The treatment setup was corrected using online correction protocol for any errors ≥ 3 mm. 231 pre-treatment CBCT scans were acquired and setup errors were recorded in left-right (LR), anterior-posterior (AP) and superior-inferior (SI) directions. The treatment setup error of ≥ 3 mm occurred in 2.2% of measurements in LR direction, 1.7% in AP direction and 6.5% in SI direction. A PTV margin of 2.96 mm, 2.55 mm and 3.30 mm in RL, AP and SI directions, respectively was calculated using Van Herk formula, when no online corrections were performed. After online correction protocol, there were no more setup errors ≥3 mm in all three directions. The PTV margin was reduced to 2.53 mm (LR), 2.39 mm (AP) and 2.81 mm (SI). Therefore, CBCT-based online correction improves the accuracy of IMRT for HNC and reduces irradiated margin by reducing both systematic and random errors.